Decision Support System for Selecting the Best Chat Application using the TOPSIS Method - Cindy Nanda Sari; Rosnizam; Mesran Mesran (International Journal of Informatics and Data Science, 2023)
Chat applications are features that allow users to send and exchange messages with others using an internet connection as a means of communication. However, with the increasing number of chat application features available today, smartphone users often complain and feel confused when choosing the best chat application feature. Considerations need to be made in determining the best chat application feature to help smartphone users find solutions to handle incompatible chat application features. With chat application features, individuals can communicate over long distances without worry, as chat applications not only support text-based communication but also enable image sharing, text messaging, voice messages, and video calls. This research involves five criteria: storage, security, user interface, application features, and network usage. The Decision Support System (DSS) aims to facilitate and solve problems by selecting the best chat application through the TOPSIS method. The result of the highest ranking is WhatsApp with a score of 0.9113. The use of the TOPSIS method in this research helps generate the best alternative with accurate and high-quality values.